INTERNALIZATION VALUE OF LOVE COUNTRY HOMELAND THROUGH NATIONAL ANTHEMS FOR EDUCATING NATIONALISM CHARACTER: (Study of habitual activities in singing national anthems at SMPN 2 Sumber-Cirebon) (International Conference on Elementary Education, 2018)
The influence of globalization has resulted in thedegradation the nationalism value among young and students. If it is left and not been filtered well the people of Indonesia would lose their identities. Based onit our Education and Cultureministry (Kemendikbud) made policy by making the educational character programs and issued an instruction to sing national anthems in education practices as an effort to inculcate character valuesback to thestudents. Education practice is proper place in internalization the nationalism value. This study aims to analyze the process of embedding the nationalism value through the national anthems media who sang songs in inuring activities at SMP N 2 Sumber. In order to detach and analyze this researcher used a qualitative approach through a method of descriptive .The purpose of the approach and that method was to analyze data by means of described or designated the data that has been collected as the fact field. The research results showed that the cultivation of the nationalism value through a program inuring activities within singing national anthemsat SMPN 2 Sumber could not yet be affecting character of students .The research finding describes the students at SMPN 2 Sumber are not ready to do this educational character programme .This statement can be proven from the findings of this field that; 1 ) there is no well-structured and systematic from the teacher or school; 2 ) when the processing habitual activities , teachers did not stimulate and intervene the students, so that they found difficulty to understand the value inside of national anthems. As a education character media, the habituation activity in singing national anthems must be implemented with well-structured and systematic design in order to accomplish a purpose program that has been formulated by the Education and Culture ministry, that isto embed nationalism values through singing national anthems at school.